Dynamics of the Darul Dakwah Wal Irsyad Foundation Educational Institution in the Aspects of Islamic Educational Management - Mukti, Abdul; Ansori, M. Afif; Andari, An An; Husaini, Muhammad Al (Graduate Program Magister Manajemen Pendidikan, 2024)
The dynamics of growth and development of Madrasa Tsanawiyah Darud Dakwah Wal Irsyad Palu are covered in this research from an educational management perspective. The methodologies used in research are library research. Data is collected based on books, journal, written works, including research results both published and unpublished. The aim of this research is to evaluate and examine the dynamics of the expansion and progress of the Temporary Darud Dakwah Wal Irsyad Madrasa Tsanawiyah (1969–2013). The study’s findings suggest that the dynamic growth of Darud Dakwah Wal Irsyad Madrasa Tsanawiyah year over year year from 1969 to the present not seeing any notable expansion. Several things have been done, such as exploring the hamlet to look for prospective students, disseminating information, and promoting the local community. However, the results did not show significant progress. Several factors that influence this include: Planning has not been integrated with the planning function. Through coordination between the Darud Dakwah Wal Irsyad of Regional Management and Darud Dakwah Wal Irsyad Madrasa Tsanawiyah, the implementation function remains unchanged while the supervision function continues to run simultaneously. It seems that the implementation of this function is carried out simultaneously with both the internal control monitoring duties carried out by the head of Madrasa Tsanawiyah, Darud Dakwah Wal Irsyad Palu, and the exterior supervision carried out by the Regional Management of the Madrasa Committee and Darud Dakwah Wal Irsyad.